2020
DOI: 10.4103/joacp.joacp_183_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of King's vision videolaryngoscope and glidescope on hemodynamic stress response to laryngoscopy and endotracheal intubation

Abstract: Background and Aims: We hypothesis that the use of novel airway devices would decrease hemodynamic stress response (HDSR) to laryngoscopy and endotracheal (ET) intubation. The aim of our study was to evaluate the hemodynamic stress response (HDSR) to laryngoscopy and tracheal intubation using the King vision video laryngoscope (KVVL) versus glidescope (GLS). Material and Methods: A prospective randomized, comparative study that was conducted on 80 patients of both sexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Using a king video laryngoscope or a glide scope, hemodynamic alteration after laryngoscopy and intubation were studied, and both were found effective in attenuating the stress response. 15 In a similar study, a single-time use video laryngoscope was compared with a Macintosh laryngoscope as in our study. The hemodynamic stability following laryngoscopy and endotracheal intubation was more pronounced when AirTran was used than Macintosh.…”
Section: Discussionmentioning
confidence: 96%
“…Using a king video laryngoscope or a glide scope, hemodynamic alteration after laryngoscopy and intubation were studied, and both were found effective in attenuating the stress response. 15 In a similar study, a single-time use video laryngoscope was compared with a Macintosh laryngoscope as in our study. The hemodynamic stability following laryngoscopy and endotracheal intubation was more pronounced when AirTran was used than Macintosh.…”
Section: Discussionmentioning
confidence: 96%
“…Traditional anesthesia requires endotracheal intubation, and there are many receptors in the throat. Direct endotracheal intubation can cause intense stimulation, leading to arousal of sympathetic nervous system and aggravation of cardiovascular stress response, which may aggravate coronary heart disease in patients [ 12 ]. The results of this study found that, at T1-T4, the levels of MAP and HR in the two groups first decreased and then increased, and the observation group was higher than the control group.…”
Section: Discussionmentioning
confidence: 99%